THE EFFECT OF DIGITAL MARKETING, CUSTOMER RELATIONSHIP MARKETING AND PRICE ON PURCHASE DECISIONS AND PURCHASE INTEREST THROUGH BRAND IMAGE AS AN INTERVENING VARIABLE AT LABUAN CAFE, BRONDONG DISTRICT (STRUCTURAL EQUATION MODELING (SEM) METHOD – PARTIAL LE - Whyudi, Frengky; Sutinem; Muhtarom, Abid; Yaskun, Mohammad (Proceeding ICAMEKA: International Conference Accounting, Management & Economics Uniska, 2025)
In the era of globalization, the business world, particularly SMEs, is growing rapidly, accounting for 99% of all business units in Indonesia (Coordinating Ministry for Economic Affairs, 2022). Fierce competition also exists in the culinary industry, including cafes in Brondong District, with many new cafes offering their own unique offerings. Cafes are now popular places for gatherings, working, and meetings, making marketing strategies key to attracting customers. This research uses a quantitative approach with a sample size of 912. The analysis method used is SEM with Smart PLS version 3.0. The tests used are the Outer Model Test, the Inner Model Test, the Mediation Test, and the Hypothesis Test. The Validity test results show that the Factor Loading value is greater than 0.7 and the AVE value is greater than 0.5, indicating validity. In the Reliability test, Composite Reliability and Cronbach’s Alpha values above 0.7 are considered reliable. It can be concluded that the Digital marketing variable has a positive and significant influence on purchasing decisions, Digital marketing has a positive and significant influence on purchasing interest, Digital marketing has a positive and significant influence on brand image, Customer relationship marketing has a positive and significant influence on purchasing decisions, Customer relationship marketing has a positive and significant influence on purchasing interest, Customer relationship marketing has a positive and significant influence on brand image, Product quality has a significant positive influence on purchasing decisions Product quality has an insignificant positive influence on purchasing interest Product quality has a significantly positive influence on brand image Price has a negative and insignificant influence. on purchasing decisions. Price has a negative and insignificant influence on purchase interest. Price has a positive and significant influence on brand image. Brand image has a positive and significant influence on purchasing decisions, Brand image has a positive and significant influence on purchasing interest